1992
DOI: 10.1111/j.1432-1033.1992.tb16894.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of Physarum polycephalum DNA‐polymerase‐α‐primase by poly(l‐malate) and related polyanions

Abstract: Poly(L-malate) is an unusual polyanion found in nuclei of plasmodia of Physarum polycephalum. We have investigated, by enzymatic and fluorimetric methods, whether poly(L-malate) and structurally related polyanions can interact with DNA-polymerase-a-primase complex and with histones of P. polycephalum. Poly(L-malate) is found to inhibit the activities of the DNA-polymerase-a-primase complex and to bind to histones. The mode of inhibition is competitive with regard to DNA in elongation and noncompetitive in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
(7 reference statements)
2
32
0
Order By: Relevance
“…Structurally, poly(α,β-(D,L)-aspartic acid) and poly(α,β-(D,L)-malic acid) are similar except the replacement of the amido group in PAA by the ester group in PMLA. Remarkably, the spatial distances of polymer pendant carboxylates are similar, which was recognized in experiments measuring the inhibition of DNA polymerases by polyanions of variable structures [44]. In this study, a similarity of the distance between the negatively charged carboxylates in PMLA and PAA with phosphate groups in nucleic acids has been noted.…”
Section: Examples Of Covalent Nanodelivery Systems Based On Polymesupporting
confidence: 70%
See 1 more Smart Citation
“…Structurally, poly(α,β-(D,L)-aspartic acid) and poly(α,β-(D,L)-malic acid) are similar except the replacement of the amido group in PAA by the ester group in PMLA. Remarkably, the spatial distances of polymer pendant carboxylates are similar, which was recognized in experiments measuring the inhibition of DNA polymerases by polyanions of variable structures [44]. In this study, a similarity of the distance between the negatively charged carboxylates in PMLA and PAA with phosphate groups in nucleic acids has been noted.…”
Section: Examples Of Covalent Nanodelivery Systems Based On Polymesupporting
confidence: 70%
“…Polymalic acid of high molecular weight was discovered by its ability to mimic nucleic acids and competitively inhibit DNA polymerase α of Physarum polycephalum , and, to a lesser extent, the activities of DNA polymerases from other organisms [43, 44] (Fig. 3).…”
Section: Examples Of Covalent Nanodelivery Systems Based On Polymementioning
confidence: 99%
“…Subsequent work showed that the slow addition of histone made it possible to assemble nucleosomes without the histone chaperone at near physiological ionic strength. Under these conditions, however, nucleosome assembly could be stimulated by the addition of other chromatin components (e.g., the linker histone H1 and the non-histone protein HMG [7,8]) and acidic polymers (e.g., acidic polypeptide [9,10], poly (L-malate) [11], and RNA [12]). These studies resulted in the isolation of other histone chaperones with different primary structures and demonstrated that there are various types of histone chaperones [13].…”
Section: Histone Chaperonesmentioning
confidence: 99%
“…for DNA polymerases) and is therefore assumed to be involved in DNA replication. [17] The organisms most efficient in producing β-PMA are the black yeasts Aureobasidium sp. [18] and A. pullulans, [19] from which up to 61 g/l and 9.8 g/l culture medium were isolated, respectively.…”
Section: Introductionmentioning
confidence: 99%